Institutionalization of Regional Policy and the Regional Institution System in Serbia - Takács, Zoltán; Nagy, Imre (European Spatial Research and Policy, 2013)
This study summarizes aspects of Serbian regional policy with special focus on regions and the development of the regional institutions. The study emphasizes the importance of the issue in the Republic of Serbia in 2010, with the ambition to join the European Union. With the enactment of the new Law on Regional Development and the legal framework five NUTS 2 regions were created. The Ministry of Economy and Regional Development is responsible for the institutional coordination of the regional policy. Regional Development Agencies are at the intermediate level of institutional hierarchy. After the regionalization of Serbia, the Autonomous Province of Vojvodina remained a whole and unified NUTS 2 region with complex and developed regional institutions.